Influential Financial Factors of Employee Engagement Outcomes within SME Business in Malaysia: A Qualitative Study - Rashid, Safiah; Mohd Harif, Mohd Amy Azhar (Journal of Business Management and Accounting, 2016)
A great deal of interest in employee engagement has been witnessed over the years. Even though previous researchers have established the relevance of employee engagement and  their  desired  outcomes,  an  examination  of  the  existing  literature  has  revealed  a gap.  Against  the  backdrop  of  the  importance  of  employee  engagement  within  small-and-medium enterprises (SMEs), the purpose of this study was to qualitatively explore employee engagement outcomes at the organisational level, particularly the influential financial factors. Participants of this study shall include the top managers of SMEs in Malaysia. Eight financial factors namely profitability, productivity, revenue, business growth, account receivable, shrinkage, operating margin, and return-on-asset (ROA) were identified. This study will employ the snowball sampling technique and converging interviewing was suggested to be used to gather data to confirm the proposed conceptual framework. Finally, data will be analysed using content analysis.
Keywords: Employee engagement outcomes; qualitative; top managers; financial factors; SMEs; Malaysia